Ileal duplication cyst: a rare cause of intestinal obstruction in infants - Basak, Aniruddha; Ghosh, Arindam; Mishra, Prafulla Kumar (International Journal of Contemporary Pediatrics, 2020)
Ileal duplication cyst (IDC) is a rare congenital anomaly where there is an abnormal portion of intestine attached to or intrinsic with the normal bowel. A 6-month-old male child presented with obstipation and bilious vomiting at emergency. X-ray abdomen showed multiple air fluid level suggestive of intestinal obstruction. Laparotomy was performed. Diagnosis of IDC was made and resection with primary anastomosis was done. Post-operative period was uneventful, and patient did well during 3 month follow-up checkup. IDC is a rare cause of intestinal obstruction which can present with different clinical symptoms posing a diagnostic dilemma. Diagnostic laparotomy is a suitable approach for both diagnosis and treatment to avoid delays in treatment where imaging method is unavailable for exact diagnosis.